Role of small private drug shops in malaria and tuberculosis programs in Myanmar: a cross-sectional study - May Me Thet; Myat Noe Thiri Khaing; Su Su Zin; Sandar Oo; Ye Kyaw Aung; Si Thu Thein (Taylor & Francis Group, 2021)
Background The role of community drug shops in providing primary care has been recognized as important in Myanmar as in other countries. The contribution by private community drug shops to National Tuberculosis case notifications and National Malaria testing and positive cases is significant. Population Services International Myanmar (PSI/Myanmar) has been successfully training and engaging community drug shops to screen presumptive Tuberculosis to make referrals to public health clinics and perform malaria rapid diagnostic tests (mRDT) to malaria fever cases and provide management accordingly. Objectives The study aims to identify barriers to service provision of the trained providers at the drug shops that are currently engaged in PSI/Myanmar Tuberculosis and malaria programs. Exploring their needs enabled us to identify and address barriers, to provide evidence for better linkage with the primary care system. Method A mixed method study was conducted with the service providers at the drug shops. A quantitative follow up survey was done with 177 trained Tuberculosis service providers and 65 trained malaria service providers. A total of 32 qualitative in-depth interviews were completed. Seventeen Tuberculosis trained providers and 15 malaria trained providers participated in individual interviews. Content analysis approach was used to generate themes for the data analysis. Results From the survey, the majority of drug shops reported that they performed appropriate first steps, particularly referring symptomatic Tuberculosis cases and offering mRDT testing to fever cases. Nevertheless, in-depth interviews with them revealed they did not adhere to the national guidelines for every client. There was a need to emphasize the importance of following the national guidelines for referring patients with prolonged cough and fever cases management. For those who were trained in Tuberculosis case referral, support from program staff was needed to make smooth referrals. Those who were trained in malaria often considered differential diagnosis of fever other than malaria and did not test with malaria rapid diagnostic test due to declining numbers of malaria cases. Conclusion The study findings highlighted that the drug shops trained in Tuberculosis referral seemed to have the potential to fully engage into the primary care health system if provided with suitable support and supervision. On the other hand, those trained in malaria case management might be less motivated to engage in the era of declining malaria endemicity.